Effects of cryotherapy after soft tissue injury: a systematic review - Mohd Radzi, Ahmad Afif Aiman; Mohamad, Mohd Yusof (IIUM Press, 2022)
Background: Cryotherapy or ice therapy is used worldwide among medical professionals and layman to treat soft tissue injuries (STI). Despite its vast usage, disputing reports, on the effectiveness of cryotherapy existed in treating STI. Therefore, this study aims to review the effects of cryotherapy on pain reduction and time taken to return to normal activity after soft tissue injury. Methods: The review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Allthe articles published in English-language within the year 2016 to 2021 were selected using databases, namely, Science Direct, PubMed, and Cochrane library. The risk of bias was assessed according to the handbook of Revised Cochrane Risk-of-Bias Tool for Randomized Trials. Results: Only 3 articles out of 178 articles fulfilled the inclusion criteria and were included for the systematic review. Only one article has some concerns of bias while the rest were low risk . Significant difference can be seen in terms of pain measured in VAS score when cryotherapy is applied either alone or together with manual therapy (p<0.05). One hundred and sixty-one patients who received cryotherapy out of 179 patients from 3 articles reported an average of 2.3 VAS score reduction from their initial score. However, there were no study that specifically include time taken to return to normal activity as an outcome measure. Conclusion: Cryotherapy is practical in treating soft tissue injuries, but it is recommended to incorporatemanual treatments and exercises to achieve normal functional ability. Keywords:cryotherapy, ice therapy, soft tissue injuries, return to activity